The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10646-010-0483-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biological effects of pollutants in a hyper eutrophic tropical water body, Lake Beira, Sri Lanka using multiple biomarker responses of resident fish, Nile tilapia (Oreochromis niloticus)

Abstract: Biomarkers measured at the molecular and cellular level in fish have been proposed as sensitive "early warning" tools for biological effect measurements in environmental quality assessments. Lake Beira is a hypertrophic urban water body with a complex mixture of pollutants including polycyclic aromatic hydrocarbons (PAHs) and Microcystins. In this study, a suite of biomarker responses viz. biliary fluorescent aromatic compounds (FACs), hepatic ethoxyresorufin O-deethylase (EROD) and glutathione S-transferase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
0
6
1
Order By: Relevance
“…Histopathological biomarkers are valuable as early indicators of the biological damage in fish as they reflect the effects of exposure to a variety of anthropogenic pollutants (Pathiratne et al 2010;Kumar et al 2017). The liver is the main site of biotransformation of foreign chemicals that enter the fish body.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological biomarkers are valuable as early indicators of the biological damage in fish as they reflect the effects of exposure to a variety of anthropogenic pollutants (Pathiratne et al 2010;Kumar et al 2017). The liver is the main site of biotransformation of foreign chemicals that enter the fish body.…”
Section: Resultsmentioning
confidence: 99%
“…Erythrocytic micronuclei and nuclear abnormalities in fish are cellular level biomarkers for assessing genotoxic effects (Al-Sabti and Metcalfe 1995;Pathiratne 2016, 2017). The liver is a vital organ and analysis of liver histological alterations in fish can be used as a tissue level biomarker for assessing organ damage (Pathiratne et al 2010;Ghisi et al 2016;Kumar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…GPx, glutathione‐S‐transferase (GST), free radicals and peroxides play a central role in the defence mechanisms against many xenobiotics and carcinogens (Data, Sinha & Chattopadhyay ). Further studies addressing changes in antioxidant and detoxification enzymes such as GPx and GST activities and gene expression of these markers would elucidate mechanisms of action in the antioxidant defence system alterations in tilapia (Pathiratne, Pathiratne & De Seram ; Puerto, Gutierrez‐Praena, Prieto, Pichardo, Jos, Miguel‐Carrasco, Vazquez & Camean ). We found that liver GSH levels were unchanged after DBP exposure during 24 and 96 h in all groups ( P > 0.05, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…GSH is an important intracellular tripeptide with diverse functions, ranging from antioxidant protection to regulation of cell proliferation. Further studies addressing changes in antioxidant and detoxification enzymes such as GPx and GST activities and gene expression of these markers would elucidate mechanisms of action in the antioxidant defence system alterations in tilapia (Pathiratne, Pathiratne & De Seram 2010;Puerto, Gutierrez-Praena, Prieto, Pichardo, Jos, Miguel-Carrasco, Vazquez & Camean 2011). Further studies addressing changes in antioxidant and detoxification enzymes such as GPx and GST activities and gene expression of these markers would elucidate mechanisms of action in the antioxidant defence system alterations in tilapia (Pathiratne, Pathiratne & De Seram 2010;Puerto, Gutierrez-Praena, Prieto, Pichardo, Jos, Miguel-Carrasco, Vazquez & Camean 2011).…”
Section: Tissue Lipid Peroxidation and Glutathione As Oxidative Stresmentioning
confidence: 99%
“…The ICD, which utilizes NADP + is present in large amounts in the liver, cardiac/skeletal muscle and kidney tissues, and alterations in its serum levels have been reported to be both sensitive and specific to injuries of hepatic parenchymal cells. SDH is mainly found in the liver, though it is also present in low levels in kidney, brain, heart and spleen tissues (46,47). Therefore, serum SDH levels may serve as a sensitive and specific biomarker for predicting liver injury.…”
Section: Time -------------------------------------------------------mentioning
confidence: 99%